The Influence of Pregnant Women's Health Education on Adherence to Antenatal Care - Tamunu, Esther Novilian; Ponidjan, Tati Setyawati; Nagara, Prapty Aditya (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Background: Maternal health problems are closely related to pregnant women, which contribute a lot to the current maternal mortality rate. The number of MMR in Indonesia is 59/100,000 KH, it is still far from reaching the MDGs target and in 2015, namely 102/100,000 KH, deaths of pregnant women can be prevented if mothers Pregnant women receive good quality antenatal care. Pregnant women's compliance with antenatal care is very important because it can reduce the number of pregnancy complications. However, the prevalence of pregnant women receiving antenatal care is very low, namely with a non-compliant value of 80% and a value of 80% for non-compliance with antenatal care. 20 %). Antenatal care is a basic health service for pregnant women which must be carried out according to standards, namely at least 4 times during pregnancy.Objective: this research is to explain the influence of pregnant women's health education on antenatal care compliance.Method : This research uses a Literature Review, namely research in the form of a literature review using the results of previous research, namely from articles and books. In order to obtain data that is appropriate to the research topic, national-based journals use Google Scholar which uses the keywords pregnant women, compliance, antenatal care. With the journal requirements being searched from 2015-2020, the researcher found 6 articles used for the Literature Review.Results and Analysis: Researchers found 6 articles that were eligible and met the inclusion criteria regarding the topic discussed, namely the influence of pregnant women's health education on antenatal care compliance.Conclusion : There is an influence between pregnant women's health education on antenatal care compliance Keywords: Pregnant Women, Antenatal Care Compliance